Integrasi Pendidikan Perubahan Iklim dalam Kurikulum dan Budaya Sekolah: Studi Kasus di SMA Sukma Bangsa Lhokseumawe - Sarlivanti, Sarlivanti (Pascasarjana IAIN Lhokseumawe, 2025)
This study aims to analyse the forms and strategies of integrating climate change education into the curriculum and school culture at SMA Sukma Bangsa Lhokseumawe, as well as to assess its impact on students’ environmental literacy and character development. The research employed a qualitative approach with a case study design, focusing on an in-depth understanding of the practices of integrating climate change education within the school setting. Data was collected through in-depth interviews with the principal and teachers, classroom observations, document analysis of school policies and teaching modules, and questionnaires distributed to students. Data analysis followed the Miles and Huberman model, which includes data reduction, data display, and conclusion drawing, while validation was ensured through source and method triangulation. The findings reveal that the integration of climate change education at SMA Sukma Bangsa Lhokseumawe is systematically implemented through project-based interdisciplinary learning, the strengthening of an environmentally friendly school culture, and teacher capacity enhancement through global collaboration. The Green School Project (GSP) serves as a key catalyst in fostering students’ ecological awareness and sustainable behavior. This study concludes that synergy among curriculum, school culture, and instructional leadership is the critical factor driving the success of the climate change education model. The study recommends the development of adaptive curriculum guidelines tailored to local environmental issues and teacher training programs focused on sustainability pedagogy to enhance the implementation of climate-conscious education in schools.